DETERMINANTS OF BATTLE PASS PURCHASE INTENTION IN GENSHIN IMPACT - Tjengharwidjaja, Adryan; Keni , Keni (International Journal of Application on Economics and Business, 2024)
Mobile gaming has been a part of people’s daily activity, either as a leisure activity or a hobby. The demand for online games has been increasing because they can be played anywhere and anytime, but the mobile gaming industry still faces challenges in generating revenue because customers tend to only use the free features of the game. Therefore, this study aims to analyze the influence of enjoyment, social value and continued use intention towards purchase intention of a virtual item in a mobile game, which is Battle Pass offered by Genshin Impact. This research is a descriptive study which describes the variables in a situation of interest of the researcher. Moreover, this is a cross-sectional study, whereas data was gathered once during a period from a specific group. This study collected data from 126 respondents in Jakarta who have purchased the Battle Pass, but only 98 data are valid for analysis. The questionnaires were distributed online and data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. This study concluded that enjoyment, social value and continued use intention can predict purchase intention positively and significantly. Based on the results, researchers hope that Genshin Impact developer (Hoyoverse) can get more information to create a strategy to increase customers’ battle pass purchase intention.